Jiuchu "Sirenbang" renxin dakuai,tongda luoshuigou yongyuan jinji - Zhao Songsheng
'Ferreting out the "Gang of Four" to the satisfaction of the people, be merciless with bad people even if they're down and continue to advance on the enemy'. Print no. 8116.752.